2016
DOI: 10.1063/1.4964835
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced performance increase of silicon heterojunction solar cells

Abstract: Silicon heterojunction solar cells consist of crystalline silicon (c-Si) wafers coated with doped/intrinsic hydrogenated amorphous silicon (a-Si:H) bilayers for passivating-contact formation. Here, we unambiguously demonstrate that carrier injection either due to light soaking or (dark) forward-voltage bias increases the open circuit voltage and fill factor of finished cells, leading to a conversion efficiency gain of up to 0.3% absolute. This phenomenon contrasts markedly with the light-induced degradation kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
54
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 45 publications
9
54
1
3
Order By: Relevance
“…4b. Light-soaking improved the conversion efficiency by about 0.3% absolute, in agreement with the recent findings of Kobayashi and colleagues 31 . With this measurement, we demonstrated a maximum conversion efficiency of 22.9% for the tunnel-IBC solar cell.…”
Section: High-e Ciency Proof-of-concept Tunnel-ibc Solar Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…4b. Light-soaking improved the conversion efficiency by about 0.3% absolute, in agreement with the recent findings of Kobayashi and colleagues 31 . With this measurement, we demonstrated a maximum conversion efficiency of 22.9% for the tunnel-IBC solar cell.…”
Section: High-e Ciency Proof-of-concept Tunnel-ibc Solar Cellssupporting
confidence: 92%
“…Our best tunnel-IBC solar cell, realized with a single alignment step and no photolithographic patterning, has a conversion efficiency >22.5%, which improves slightly after light-soaking 31 .…”
mentioning
confidence: 96%
“…Furthermore, a‐Si:H cells are well known to undergo LID through the Staebler‐Wronski effect. Notably, whereas it has been shown that LID can cause some degradation of intrinsic a‐Si/c‐Si interface passivation structures, it was recently found that, on the device level, SHJ cells actually improve their efficiency under light exposure …”
Section: Discussion and Outlookmentioning
confidence: 99%
“…This is most likely due to dopant‐induced defect generation in a‐Si:H layers . Remarkbly, such stacked films, featuring a doped layer, lead to improved passivation upon extended light soaking, resulting in improved efficiencies of finalized devices …”
Section: Status Of High Efficiency Shj Cellsmentioning
confidence: 99%
“…The development of surface passivation and interface control schemes is essential for the development of semiconductor technologies, such as Si solar cells and high electron mobility transistors (HEMTs) . Passivation strategies for high‐vacuum and/or high‐temperature techniques, such as Al 2 O 3 , SiO 2 , and hydrogenated amorphous silicon (a‐Si:H), have garnered significant attention due to their excellent passivation effects .…”
mentioning
confidence: 99%